Regulatory Harmonization in Latin American and the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
Under this agreement, IICA is partnering with USDA/FAS to support the development and adoption of harmonized science-based and trade facilitating regulatory policies by organizing specific in-country interventions and regional meetings between U.S. technical experts and in-country government delegates responsible for ensuring agricultural health and food safety standards in Latin America and the Caribbean Regions.